2019
DOI: 10.1186/s12909-019-1670-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of SNAPPS for improving clinical reasoning in postgraduates: randomized controlled trial

Abstract: Background In-patient postgraduate teaching suffers with issues like long and unstructured presentations inclusive of a lot of historical information and time constraints due to increasing workload. A six-step pneumonic SNAPPS a learner-centered model modifies the learning encounter by condensing the reporting of facts while encouraging clinical reasoning. This study was planned with the aim to evaluate the effectiveness of SNAPPS as compared to traditional case presentation for facilitating clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 12 publications
2
26
0
1
Order By: Relevance
“…Competence-based medical education is supposed to prepare medical students for clinical problem solving [ 1 ]. Focused history taking, knowledge-based clinical reasoning, and adequate case presentation represent important facets of competence which are crucial for good patient management [ 2 ], [ 3 ], [ 4 ]. To acquire these competences, communication trainings with simulated patients, seminars, and other training programs have been established in undergraduate medical education [ 5 ], [ 6 ], [ 7 ], [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Competence-based medical education is supposed to prepare medical students for clinical problem solving [ 1 ]. Focused history taking, knowledge-based clinical reasoning, and adequate case presentation represent important facets of competence which are crucial for good patient management [ 2 ], [ 3 ], [ 4 ]. To acquire these competences, communication trainings with simulated patients, seminars, and other training programs have been established in undergraduate medical education [ 5 ], [ 6 ], [ 7 ], [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…SNAPP modelinin uygulandığı çalışmada öğrenciler, öğrenme eylemlerinde aktif olduklarını, sezgisel düşünmelerinin arttığını, öğrenmelerinin kolaylaştığını belirtmişlerdir. (10) Uzmanlık eğitiminde SNAPPS modeli ile geleneksel olgu sunumlarının karşılaştırıldığı randomize klinik çalışmada, modelin tanı hipotezleri oluşturma, ayırıcı tanı yapmada etkin olduğunu bildirmişlerdir (12).…”
Section: Discussionunclassified
“…Thus, the process would enable significant ‘transfer of learning’ while solving similar cases in the clinical environment [ 33 ]. Jain et al [ 34 ] conducted an open labelled randomized control experiment to test the effectiveness of a six step pneumonic centred clinical reasoning model (SNAPPS) in improving the clinical reasoning ability of postgraduates. They found that students in SNAPPS group were clearer in generating diagnostic hypothesis and because of this, they could compare and contrast the differential diagnosis in a better way compared to control group.…”
Section: Discussionmentioning
confidence: 99%